What happened to the McCrays? : a novel - Lange, Tracey (Celadon Books, 2025)
"When Kyle McCray gets word his father has suffered a debilitating stroke, he returns to his hometown of Potsdam, New York, where he doesn't expect a warm welcome. Kyle left suddenly two and a half years ago, abandoning the people who depended on him: his father, his employees, his friends--not to mention Casey, his wife of sixteen years and a beloved teacher in town. He plans to lie low and help his dad recuperate until he can leave again, especially after Casey makes it clear she wants him gone. The longer he's home, the more Kyle understands the impact his departure has had on the people he left behind. When he's presented with an opportunity for redemption as the coach of the floundering middle school hockey team, he begins to find compassion in unexpected places. Kyle even considers staying in Potsdam, but that's only possible if he and Casey can come to some kind of peace with each other"--Inside jacket flap.